Primary pyogenic ventriculitis caused by Streptococcal pneumoniae in adults - Chavada I Jayendrakumar; Dinesh B Ganesan; Siddhant J Thampi; Vasanthi Natarajan (Journal of Family Medicine and Primary Care, 2019)
Primary pyogenic ventriculitis is more commonly manifested in children. Its presentation in adults due to Streptococcus pneumonia is rarely reported. It is mainly due to adequate vaccination cover and initiation of appropriate antibiotics. Ventriculitis is one of the complications of bacterial meningitis, requires long-term antibiotics and surgical intervention. Here, we are reporting a 67-year-old diabetic lady presented with a decrease in sensorium, seizure, and fever, diagnosed as bacterial ventriculitis. Her cerebro spinal fluid (CSF) picture suggestive of pyogenic meningitis, CSF, blood culture grew Streptoccous pneumoniae; MRI revealed –ventriculitis. She was treated with Injection Ceftriaxazone for 6 week duration. Serial MRI showed clearing of ventricular debris and she improved.This highlights the atypical presentation of pyogenic meningitis without nuchal rigidity, status epilepticus, and clinical improvement without the need of surgical intervention.